Improved Efficiency of Lutein Extraction from Hens’ Feed Mixture and Food Samples Using Less Toxic Solvent Mixture - Olivera Galović; Doris Prokopec; Zlata Kralik; Manuela Košević; Gordana Kralik (Applied Sciences)
Lutein is one of the nutrients necessary for the proper functioning of our organism. The majority of research focuses on the impact of lutein on eye health and its role as an antioxidant. Although fruits and vegetables are the most important sources of lutein, chicken eggs are considered an excellent and widely used source, necessitating the determination of lutein concentration in food. One of the methods for extracting lutein from various food samples is solvent extraction. Although it is one of the older methods and has disadvantages compared to instrumental methods, it is still widely used. In this investigation, the adapted AOAC method developed by Leeson et al. (used here as a standard method), was modified by adjusting the composition of the extraction solvent mixture in order to reduce the amount of toxic solvents used. The mixture of hexane:acetone:ethanol:toluene (10:7:6:7, v/v/v/v) was replaced with a mixture of methanol:acetone (1:1, v/v). The concentration of lutein extracted from the hens’ feed mixture was 52% higher compared to the method developed by Leeson et al. The suitability of the modified method was tested on two parallel samples, and the obtained recovery values were 95.68% and 98.38%, respectively. The influence of ultrasound on lutein extraction was examined, but the obtained concentration of lutein was 8.66% lower than the concentration determined by the modified standard method. The modified standard method was then used to determine lutein concentration in six hens’ feed mixture samples and eight food samples. The results obtained were in accordance with the data from the literature.